Patients' perception of the quality of eye care at the University College Hospital, Ibadan (2005)
Objective: To determine patients' perceptions about the quality of care and possible factors that may prevent adequate utilization of services at the study centre and therefore make recommendations for improvement in service utilization. Materials and methods: A cross sectional survey of patients from the Eye Clinic and Eye Ward of the University College Hospital, Ibadan, was carried out using a standardized questionnaire between May and June 2001. Results: A total of fifty respondents were interviewed: 33 (66%.) were male, while 17 (34%) were female. Their ages ranged from less than 10 years to more than 80 years, with a mean age of 46.5 years. The majority of the patients (78%) lived within Ibadan, while 22% lived outside Ibadan. Over half of the respondents (56%) were gainfully employed. Others included retirees (20%) and students (20%). Thirty-eight of the respondents (88%) experienced some obstacles before and/or on presentation at the hospital. Notable obstacles to the optimal use of facilities include: frequent strikes embarked on by hospital workers (66% of respondents), long wait before seeing the eye doctor as reported by 36% of respondents; high cost of services 8%, fear of the outcome of surgery reported by 12% of those who had surgery; and the unfriendly attitude of some staff. Recommendations by respondents for improving the quality of health service delivery include: provision of more equipment in the eye clinic (68%) and the employment of more eye doctors (64%). Other suggestions include reduction in the cost of surgery and other services (12%), and the need for records staff and nurses to be more humane and show understanding to patients, especially those from out of town (4%).